The Correlation between Diabetes Mellitus and Neurodegenerative Diseases - Schubert, Markus (Klinische Monatsblätter für Augenheilkunde, 2023)
Today there is no longer any doubt that diabetes mellitus is associated with cognitive impairment and neurodegenerative diseases. The two most common forms of diabetes mellitus are type 1 and type 2. Type 1 diabetes mellitus is characterized by an absolute insulin deficiency that is associated with a large number of metabolic changes. This type of diabetes requires insulin therapy. Without insulin, this disease is fatal. The far more common form of diabetes mellitus nowadays is type 2 diabetes mellitus. It is characterized by insulin resistance. For a number of years drugs have been available that can be used to treat this form of diabetes in a multimodal manner. These therapy options can not only improve metabolic control, but also prevent cardiovascular events. Different cognitive alterations associated with diabetes mellitus can be distinguished. On the one hand, the change in glucose homeostasis itself leads to cognitive alterations, i.e. blood sugar levels that are too high or acutely too low are regularly associated with significant impairments in mental performance, including loss of consciousness. But not only the momentary blood sugar levels, but also long-term changes in glucose metabolism might lead to neurodegeneration and even dementia in a way that has not yet been fully understood. Insulin or insulin-like molecules have important effects in the central nervous system. In the last decades, it has been shown that insulin receptors themselves are expressed in many regions of the brain and e.g. regulate food intake and memory formation in humans and in animal models. In the animal model, disturbances in insulin signal transduction influence the development of pathologies typical of Alzheimerʼs disease (AD). In humans, central insulin resistance is at least part of the formal pathogenesis of AD. Vascular changes (macroangiopathy) in patients with diabetes mellitus often lead to cerebral insults, microangiopathies and vascular dementia.Es besteht heute kein Zweifel mehr, dass der Diabetes mellitus mit kognitiven Leistungseinschränkungen und neurodegenerativen Erkrankungen assoziiert ist. Die beiden häufigsten Formen des Diabetes mellitus sind der Diabetes mellitus Typ 1 und 2. Der Diabetes mellitus Typ 1 ist gekennzeichnet durch einen absoluten Insulinmangel, der mit einer Vielzahl von Stoffwechselveränderungen assoziiert ist. Diese Diabetesform bedarf zwingend einer Insulintherapie. Ohne Insulin verläuft diese Erkrankung tödlich. Die heutzutage weit häufigere Form ist der Diabetes mellitus Typ 2. Dieser ist gekennzeichnet durch eine Insulinresistenz. Seit mittlerweile einigen Jahren stehen Medikamente zur Verfügung, mit der diese Form des Diabetes multimodal behandelbar ist. Diese Therapieoptionen können nicht nur die Stoffwechseleinstellung verbessern, sondern auch kardiovaskuläre Ereignisse verhindern. Es können verschiedene kognitive Einschränkungen, die mit dem Diabetes mellitus assoziiert sind, unterschieden werden. Zum einen führt die Veränderung der Glukosehomöostase an sich zu kognitiven Einschränkungen, d. h., zu hohe oder akut zu niedrige Blutzuckerspiegel gehen z. T. mit erheblichen Störungen der geistigen Leistungsfähigkeit bis hin zur Bewusstlosigkeit einher. Aber nicht nur die Blutzuckerspiegel, auch langfristige Veränderungen des Stoffwechsels führen letztendlich auf noch nicht ganz geklärte Weise zu Neurodegenerationen bis hin zur Demenz. Insulin oder insulinähnliche Moleküle haben eine bedeutende Wirkung im zentralen Nervensystem. In den letzten Jahrzehnten konnte gezeigt werden, dass Insulinrezeptoren selbst in vielen Regionen des Gehirns exprimiert werden und z. B. die Nahrungsaufnahme und Gedächtnisleistung im Menschen und im Tiermodell regulieren. Im Tiermodell beeinflussen Störungen der Insulinsignaltransduktion die Ausprägung von z. B. für den Morbus Alzheimer (AD) typischen Pathologien. Beim Menschen gehört eine zentrale Insulinresistenz zumindest zur formalen Pathogenese des AD. Gefäßveränderungen (Makroangiopathie) bei Patienten mit Diabetes mellitus führen nicht selten zu zerebralen Insulten, Mikroangiopathien und vaskulärer Demenz.
Keywords: Diabetes mellitus; neurodegeneration; insulin